New Insights into Nuclear Magnetic Resonance (NMR) Spectroscopy - Ioannis P. Gerothanassis; Teobald Kupka (Molecules)
NMR spectroscopy is playing an increasing role in chemistry, biology, material sciences and related disciplines [...]